Influence of Production Technology on Selected Polymer Properties - Ponikelsky, Josef; Zuravsky, Igor; Cernohlavek, Vit; Cais, Jaromir; Sterba, Jan (Manufacturing Technology Journal, 2021)
In the article, the study of polymer properties is dealt with as a result of production technology on pat-terns, which were made by injecting, machining of the extruded profile and 3D printing. All samples were made from iglidur(R) J260 material, and they were subsequently tested in order to find out properties of roughness, breaking strength, hardness according to Shore, friction coefficient and swelling. Further-more, the samples were exposed to light microscopy, where material structure was studied, especially from the view of structure defects, distribution and shape of solid lubricants. Based on the performed experiment, it can be stated that production technology affects some properties of the sliding bushing. Above all, properties of the sliding bushing were affected by 3D printing technol-ogy. The measured samples had the worst results with regard to roughness and swelling values. Con-versely, the values acquired by measuring hardness were surprising as the 3D priting samples reached better results than the samples made by machining. The samples created by injection had the best re-sults compared to others in all tests. The measured values corresponded to the values listed by the man-ufacturer. Machined sample of the extruded profile is mainly affected by the type of machining, but with consideration to the structure, it can be claimed that the extruded material has the same structure as an injected piece and its properties, with the exception of surface roughness, are on the same level.
Keywords: Polymer; Injection; Extrusion; Machining; 3D printing